齿轮轮齿表面粗糙度的评定分析与质量控制 - 罗太景 (Jixie chuandong)
The evaluation method of the gear tooth sueface quality and the definition of the tooth surface roughness are introduced.The evaluation method of the gear tooth surface roughness is proposed. Taking contact sensor instrument,for example,the evaluation method of measuring the tooth rouhness is analyzed.